Proceedings of the 1st Paris Van Java International Seminar on Health, Economics, Social Science and Humanities (PVJ-ISHESSH 20 2021
DOI: 10.2991/assehr.k.210304.054
|View full text |Cite
|
Sign up to set email alerts
|

‘This is My Fault, but Now I Know Online Game Addiction Is Not Good for Me’: School Dropped Out Students’ Narrative

Abstract: School dropped-out students have attracted educators and policy makers. A number of studies have investigated factors and number of the dropped out students. However, albeit of these studies, dropped out students' voice was reported. Thus, this paper is aimed at portraying dropped out student' voice. Their reason for dropping out and their wishes were sought. Of 114 respondents, three respondents were voluntarily recruited for an interview. The findings revealed they unintentionally opted for dropping out but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Even though there are research and cast study to attempts using video game as learning media such as shown by Ng, (2019); Pane et al, (2017); Sijabat & Grahita, (2022); Tamtama et al, (2020), negative sentiment still prevalent in Indonesia. Research by Aisyah et al, (2021) blame online video games as the main reason why students drop out their education. Another research by Muslem et al, (2018) mention that albeit teacher agree that ICT support the learning process but refuse to remove the role 'teacher' because of using ICT is considered less important that how the teacher teach the student.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Even though there are research and cast study to attempts using video game as learning media such as shown by Ng, (2019); Pane et al, (2017); Sijabat & Grahita, (2022); Tamtama et al, (2020), negative sentiment still prevalent in Indonesia. Research by Aisyah et al, (2021) blame online video games as the main reason why students drop out their education. Another research by Muslem et al, (2018) mention that albeit teacher agree that ICT support the learning process but refuse to remove the role 'teacher' because of using ICT is considered less important that how the teacher teach the student.…”
Section: Literature Reviewmentioning
confidence: 99%